Garnet-biotite pair: a suitable geothermometer (Journal of Nepal Geological Society, 2017)
The garnet-biotite pairs are commonly found in the pelitic assemblage right from upper green schist to granulites facies and hence are suitable for estimating equilibrium temperature for most metamorphic rocks. Several geothermometer has been proposed since long based on garnet - biotite Fe-Mg exchange reaction ‘1/3 Almandine + 1/3 Phlogopite = 1/3 Annite + 1/3 Pyrope’. The authors has developed a software in visual basic to calculate the temperature based on this pair using the formulation given by different works.